Laboratory assessment of a photoactive Gypsum-based repair plaster. (5th September 2022) - Svorová Pawełkowicz, Sylwia; Svora, Petr; Prošek, Zdeněk; Keppert, Martin; Vejmelková, Eva; Murafa, Natalija; Sawoszczuk, Tomasz; Syguła–Cholewińska, Justyna; Bíbová, Hana
Graphical abstract: Highlights: Photoactive repair plaster based on CaSO4 ·½H2 O and TiO2 is described. TiO2 admixture did not affect flexural strength of the specimens. TiO2 had a slight impact on porosity, and, consequently, on compressive strength of the specimens. Good results have been obtained for NO photodegradation. The studied repair plasters showed no antimicrobial activity. Abstract: Air pollutants, such as nitrogen oxides (NO and NO2 ), have a negative impact on the built cultural heritage. In order to reduce it, a photoactive repair plaster for conservation of various gypsum decorations, in particular moulded elements, has been developed in compliance with the requirements of conservators-restorers international community. Hence, the composition of the repair plaster is based on traditional materials (plaster of Paris) with the admixture of a modern material – photoactive titanium dioxide (TiO2 ) in different weight concentrations 0.5 %, 1 %, 1.5 %, 2 %. The paper presents the results of mechanical, photoactivity and microbiological tests along with the phase analysis and a study of the microstructure of the repair plaster specimens. Several analytical techniques were applied to characterize them, such as X-ray powder diffraction (XRD) and electron microscopy (SEM, TEM) coupled with energy dispersive X-ray spectroscopy (EDS). The results show that gypsum/TiO2 repair plaster can be an effective solution for historical monuments struggling with high air pollution.